Esterase heterogeneity in selected aquarium fishes - Marquez, Charles Raiñer C. (The Mindanao Forum: official journal of the MSU-Iligan Institute of Technology, 1998)
This study was conducted to determine biochemical genetic diversity between commonly reared aquarium fish species. Esterase gene loci were evaluated based on protein products elucidated by electrophoresis. There were 11 different Isozymes identified based on the relative mobility of the bands. Based on esterase patterns, the different species were observed to be genetically-differentiated. Fish species were observed to differ from each other based on Isozymes expressed.